(untitled) (The Review of Diabetic Studies, 2024)
Background/Objectives: Medication errors (MEs) are a global healthcare concern, causing preventable harm and financial burdens. In Saudi Arabia, ME reporting by nurses remains low despite their critical role in medication administration. This study aimed to measure ME prevalence, identify reporting barriers, and explore correlations with sociodemographic factors to improve patient safety. Methods: A cross-sectional study was conducted at King Fahd General Hospital, Jeddah, involving 317 registered nurses. Data were collected via a structured questionnaire assessing ME experiences, reporting practices, barriers, and attitudes toward organizational culture. Statistical analysis included frequency distributions, chi-square tests, and one-way ANOVA. Results: Nearly one-third (29.7%) of nurses experienced MEs, yet only 25.6% reported them. Key barriers included fear of disciplinary actions (59.9%) and blame (54.3%). Nurses with >10 years of experience and those in surgical departments were more likely to report MEs. Half of participants agreed that reporting MEs is constructive, though one-third believed it could harm their careers. Conclusions: The study reveals a gap between ME occurrence and reporting, driven by fear of repercussions and inadequate reporting systems. Improving ME reporting requires transparent protocols, education, and a supportive culture. Systemic changes are needed to foster a blame-free environment, encouraging nurses to report errors and enhance patient safety.